The Think Pair Share (TPS) Learning Model on Student Learning Outcomes in Class VII Social Sciences Subjects in Pematangsiantar Private SMP - Simbolon, Rotua Maria; Siahaan, Anton Luvi; Sirait, Paulina Herlina N. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out whether there are differences in learning outcomes in the pre-literacy material in the Social Sciences Theme 2 book using the think pair share and conventional model learning models. This type of research is quantitative research carried out at the Pematangsiantar Model Private Middle School. The population in this study was all 68 class VII students. The sample in this study consisted of 2 classes, namely class VII-A and VII-B with a total of 68 people. Based on the results of descriptive analysis, it shows that the average social studies learning outcome for students in classes that do not use the think pair share learning model is 69.37. Meanwhile, the average student learning outcomes in classes that use the think pair share learning model is 80. The results of inferential statistics using SPSS version 25 obtained Sig (2 tailed) < α or (0 < 0.05) and the calculated t value > t table (4.81 > 1.996). So, based on the testing criteria, it can be said that there is a significant difference in learning outcomes between classes that use the think pair share model and classes that use the conventional learning model in class VII Praaksara material in social studies subjects at the Pematangsiantar Exemplary Private Middle School.